Quand le pas fait corps et sens avec l’espace. Aspects sensibles et expressifs de la marche en ville - Rachel Thomas (Unité Mixte de Recherche 8504 Géographie-cités, 2004)
This study takes a micro-sociological look at how pedestrians walk around towns. The aim is to highlight the various ways in which city-dwellers gain access to public places and the practical and perceptive dimensions that this accessibility calls upon. From our point of view urban mobility is based on a process by which pedestrians bond with their surroundings: mobility involves the perceptible environment of the public urban space, the perception of the pedestrian and the ability of his or her body to express itself. It is consequently necessary to characterise and describe precisely the ambient atmospheres in which such activities develop, the forms of motive action and perceptive attention they generate, and ultimately the types of relationship with the city that they bring about. Drawing on recurrent observation and description of public behaviour in the city of Grenoble this work proposes six perceptible figures of urban accessibility. Each one reflects the individual rationales of pedestrians and the special role of sensory perception in the choice of one's route across town.